2020
DOI: 10.1007/s13538-020-00787-2
|View full text |Cite
|
Sign up to set email alerts
|

Twist-Bend Nematic Phase: Role of Third-Order Legendre Polynomial Term in Chiral Interaction Potential

Abstract: Using a mean-field theory, a twist-bend nematic (N TB) phase has been described. In addition to second-order Legendre polynomial term, the chiral interaction potential includes third-order Legendre polynomial term also. It considers the coupling between a nematic director and a pitch axis of the N TB phase. The distortion free energy, order parameter for twist-bend nematic, and orientational distribution function in equilibrium state have been calculated. Based on the free energy minimization, we obtain that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…Recently, however, it was shown that some banana-shaped molecules consisting of two identical or near-identical mesogenic units connected by an oddnumbered alkyl or alkoxy chain can form, at temperatures below their nematic range, another distinct liquid crystalline phasea phase with no smectic-like translational ordering, but with a rather peculiar kind of molecular arrangement with periodic twist and bend deformation of the director distribution. Such phase seems to be first reported in [5], and was later generally recognized as the "twist-bend nematic phase" ( [6][7][8][9][10] and references therein) and designated as Ntb. In the Ntb phase, the director forms a conical helix, and chirality appears spontaneously with equal fractions of helically-ordered "domains" of opposite handedness from an achiral liquid crystal at the molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, however, it was shown that some banana-shaped molecules consisting of two identical or near-identical mesogenic units connected by an oddnumbered alkyl or alkoxy chain can form, at temperatures below their nematic range, another distinct liquid crystalline phasea phase with no smectic-like translational ordering, but with a rather peculiar kind of molecular arrangement with periodic twist and bend deformation of the director distribution. Such phase seems to be first reported in [5], and was later generally recognized as the "twist-bend nematic phase" ( [6][7][8][9][10] and references therein) and designated as Ntb. In the Ntb phase, the director forms a conical helix, and chirality appears spontaneously with equal fractions of helically-ordered "domains" of opposite handedness from an achiral liquid crystal at the molecular level.…”
Section: Introductionmentioning
confidence: 99%